Longitudinal reciprocal dynamics between teacher emotional support and EFL learners’ emotional engagement: Between- and within-person perspectives - Alrabai, Fakieh; Shirvan, Majid Elahi; Taherian, Tahereh (Studies in Second Language Learning and Teaching, 2025)
Emotional engagement (EE) has emerged as a central factor in sustaining learners’ motivation and cultivating environments that promote both academic success and personal well-being. Central to fostering EE is perceived teacher emotional support (PTES), characterized by teacher behaviors such as warmth, empathy, and responsiveness that contribute to a positive and motivating classroom climate. However, the complex and reciprocal relationship between PTES and EE remains insufficiently explored. This study seeks to address this gap through the lens of complex dynamic systems theory (CDST). Utilizing data collected over the course of a semester from 126 fourth-year English as a foreign language (EFL) learners, the study employed cross-lagged panel models (CLPM) to investigate between-person effects and random intercept CLPM (RI-CLPM) to analyze within-person dynamics. The findings revealed a reciprocal relationship: Higher levels of EE enhanced learners’ perceptions of teacher support, while greater teacher support contributed to increased EE over time. The results underscore the mutually reinforcing relationship between PTES and EE, illustrating how these dynamics vary both within and between individuals. This research offers practical insights for teachers, advocating for the creation of emotionally supportive classroom environments that enhance learner EE and ultimately contribute to greater success in second language (L2) learning contexts.